The Development Of Crossword Game Media On Virus Material - Mardiana Nata Ruron; risya pramana situmorang; Susanti Pudji Hastuti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
PENGEMBANGAN MEDIA GAME CROSSWORD PADA VIRUS MATERIALAbstractCrossword game media was a learning tool that serves features to understand the concept and solve a problem. The media provides many features that facilitate students to learn enjoyably. This study aims to develop a viable and effective product to improve students' problem-solving skills and conceptual understanding. The ADDIE model is used as a type of research and development. The subjects were students of X-grade senior high school in Salatiga. Data collection was carried out through observation, questionnaires, and tests. Media experts and material experts carried out the validation of products. Teachers were involved in giving feedback about the practicality of the media. The validation concluded that the product was feasibly based on the media aspect= 85,5% (feasible) and the material aspect = 81,25% (feasible). The product's development has improved problem-solving skills and conceptual understanding effectively that the t-test showed a significant value with acquisition sig. 2 tailed < 0,05. The results indicate that the crossword game was feasible and effective in improving problem-solving skills and conceptual understanding.AbstrakMedia crossword game merupakan salah satu media belajar siswa, menyediakan fitur untuk menjadikan siswa dapat memahami konsep dan memecahkan masalah. Crossword game menyediakan banyak fitur yang memudahkan siswa untuk belajar dengan menyenangkan. Penelitian ini bertujuan untuk mengembangkan produk yang layak dan efektif untuk meningkatkan keterampilan pemecahan masalah dan pemahaman konseptual siswa. Model ADDIE digunakan sebagai penelitian dan pengembangan. Subjek penelitian adalah siswa SMA kelas X di Salatiga. Pengumpulan data dilakukan melalui observasi, kuesioner, dan tes. Validasi produk melibatkan ahli media dan materi. Guru dilibatkan untuk memberikan umpan balik tentang kepraktisan media. Berdasarkan validasi, disimpulkan bahwa produk layak berdasarkan aspek media = 85,5% (layak) dan aspek material = 81,25% (layak). Pengembangan dari produk telah meningkatkan keterampilan pemecahan masalah dan pemahaman konseptual secara efektif sehingga berdasarkan uji-t menunjukkan nilai yang signifikan dengan perolehan sig. 2 tailed <0,05. Hasil menunjukkan bahwa media crossword game layak dan efektif dalam meningkatkan keterampilan pemecahan masalah dan pemahaman konseptual.